The educational revolution of sunan bonang through transformative islamic-javanese syncretism - Naomi Fahma (At Turots: Jurnal Pendidikan Islam, 2025)
This research analyzes the philosophical contributions of Sunan Bonang in the development of Islamic education that is integrated with Javanese culture through a religious-cultural syncretism approach. The purpose of this study is to identify the foundational principles of Sunan Bonang's educational philosophy, to analyze the methods of transmitting Islamic values within the context of Javanese culture, and to evaluate the relevance of his thoughts to character formation in contemporary Islamic education. The research questions include: (1) What is Sunan Bonang's philosophical conception of harmonizing Islamic teachings with Javanese tradition? (2) What pedagogical strategies did Sunan Bonang employ to transform Islamic values through the medium of local culture? (3) To what extent is Sunan Bonang's religious-cultural syncretism relevant to character formation in the context of modern Islamic education? The methodology employed in this research utilizes a historical-philosophical approach with hermeneutical analysis of primary texts, including Suluk Wujil and Bonang, historical manuscripts from the Walisongo period, as well as observations of contemporary cultural practices that still uphold elements of Sunan Bonang's teachings. The findings of the study indicate that: (1) Sunan Bonang developed a tawhid-based educational philosophy manifested through symbols and narratives of Javanese culture; (2) His pedagogical strategies are multilayered, integrating the traditions of gamelan, tembang, and wayang as media for the transmission of Islamic values; (3) Sunan Bonang's syncretic approach demonstrates effectiveness in the contextualization of Islamic teachings without compromising theological essence; (4) The character formation model rooted in sufistic values combined with local wisdom creates a distinctive foundation for the identity of Nusantara Islam. The results of this study provide an alternative philosophical framework for the development of contemporary Islamic education that is responsive to cultural diversity and the challenges of globalization.